The Awareness of Housewives on the Quality of Healthy Food - Salwa Muftah Eljamay; Aziza. M. Agwida ALsheek; Noor-Alhooda Milood Al Awkally; Salha Youssef Elmesoury (CV. Literasi Indonesia, 2022)
Housewives' knowledge about healthy food may influence the formation of their eating behaviors, Methods: using collecting sampling, a total of 313 housewives were recruited for the study. A questionnaire consisting of several sections was used for assessing nutrition knowledge where questions were adopted. Demographic data (Education level, age, income, and other Parameters) about nutrition education, the starting date of collection of questionnaire data was for eight months starting from 01/02/2019 to 01/11/2019. Results: the percent of married women was 62.0%, single by 19.0%, widows, by 12.2%, and divorce women by 6.1%, the percent of Economic Situation, the highest percentage for the medium by 91.0%, the graduate level high percentage of 41.2% followed by a high graduated Level of 38.3% then a Medium level with 8.3 % and who have no level of education was 12.1%, the mean and respectively, the Correlations between the awareness of housewives about the educational level and Life Style of housewives, and there was no relationship between Knowledge with Life Style & Education level that the P-Value = 0. 000, that is significant at the 0.01 level (p-value). the Education level of housewives about the Life Style of housewives that the table illustrated there was no relationship between the Education level of housewives and Life Style p-value = 0. 002, which is significant at the 0.01 level (p-value). The Life Style of housewives and the Marital Status of housewives that the P-Value = 0.005, which is significant at the 0.01 level (p-value). Conclusion: From these results, it was found that there is not a strong correlation between the extent of awareness of healthy nutrition, age, school level, and economic level, and that, there is a strong relationship between healthy food awareness and watching TV, and this indicates the importance of Education programs.